Verb Phrases and Adverbs in The Kaili Language, Rai Dialect - Fitri Fitri; Revalni Revalni; Dwi Kinanti A. Puangolo; Odhy Amalia (Civiliza Publishing, Indonesia., 2026)
This study discusses verb and adverbial phrases in the Kaili Rai Dialect Language, with the formulation of the problem in this study is how the structure of verb phrases, how is the form of adverb phrases and how is the function of adverb phrases in the Kaili Rai Dialect language, Sipeso Village, Sindue Tobata District, Donggala Regency. Based on the formulation of the problem, this research aims to describe how the structure, how it is formed, and how the function of the rai dialect kaili language. This research is a type of qualitative research. The data collection technique is carried out using the listening method, capable of data analysis which is used to match and distribute. The location of this research is in Sipeso Village, Sindue Tobata District, Donggala Regency. The data obtained is in the form of oral data obtained through data collection techniques. Furthermore, the data was analyzed using descriptive techniques. From the results of the study, it was found that in the Kaili language of the Rai dialect the Intransitive verb phrase and the modified type Adverb phrase are divided into three types, namely (1) intransitive verb phrase and H-H-type modative Adverb phrase, (2) intransitive verb phrase and H-T modifiative type Adverb phrase, (3) intransitive verb phrase and T-H-H modifiative type Adverb phrase, (4) intransitive verb phrase and T-H-T modative type adverb phrase. Likewise, monotransitive verb phrases in the Kaili Diaek Rai language, the structure of their functions is divided into three types, namely (1) monotransitive modifiative type verb phrase H-H, (2) monotransitive modifiative type verb phrase T-H, (3) monotransitive modifiative type verb phrase H-T, (4) monotransitive type verb phrase T-H-T. From the results of the study, it was also found that the function of adverb phrases is determined by variations in their structural patterns, namely in the patterns H-H, H-T, T-H, and T-H-T.